Pharmacist Preceptor Exposure, Comfort and Awareness of Resources to Address the Social Determinants of Health-A Pilot Study - Tyler Marie Kiles; Karl R. Kodweis; Christa George; Chelsea Danielle Watts; Adalis Lock; Catherine Crill (MDPI AG, 2023)
As preceptors are responsible for the experiential education of future pharmacists, it is important to assess understanding and identify knowledge gaps for preceptor development. The purpose of this pilot study was to assess the exposure to social determinants of health (SDOH), comfort in addressing social needs, and awareness of social resources among the preceptors at one college of pharmacy. A brief online survey was sent to all affiliated pharmacist preceptors with screening criteria for pharmacists who had regular one-on-one patient interactions. Of 166 preceptor respondents (response rate = 30.5%), 72 eligible preceptors completed the survey. Self-reported SDOH exposure increased along the educational continuum (with increasingly more emphasis from the didactic to experiential to residency). Preceptors who graduated after 2016, practiced in either community or clinic settings and served >50% of underserved patients were the most comfortable addressing social needs and the most aware of social resources. Preceptor understanding of SDOH has implications for their ability to educate future pharmacists. Colleges of pharmacy should evaluate practice site placement as well as preceptor knowledge and comfort in addressing social needs in order to ensure that all students are exposed to the SDOH throughout the continuum of learning. Best practices for up-skilling preceptors in this area should also be explored.